2018
DOI: 10.1371/journal.pone.0196561
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of fine needle aspiration cytology at Kamuzu central hospital

Abstract: BackgroundFine needle aspiration cytology (FNAC) has been widely accepted to be a safe, accurate, prompt and inexpensive procedure for diagnosis of both neoplastic and infectious diseases in adult and pediatric populations. Despite its value for diagnosis, FNAC is underutilized in resource limited countries. We reviewed the utilization of FNAC after it was introduced at Kamuzu Central Hospital (KCH).MethodsA retrospective review of all FNAC performed at KCH laboratory during the period of January 2012 to July … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…Undesirable aspirates were due to insufficiently trained cytopathologists and poor handling of the aspirated material [28]. It has been reported that FNAC has more diagnostic accuracy when performed by an experienced pathologist, in comparison to the other clinicians [1]. This finding is in accordance with other studies that have shown that the success of FNAC highly depends on the training and experience of the personnel conducting the procedure [28,29].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Undesirable aspirates were due to insufficiently trained cytopathologists and poor handling of the aspirated material [28]. It has been reported that FNAC has more diagnostic accuracy when performed by an experienced pathologist, in comparison to the other clinicians [1]. This finding is in accordance with other studies that have shown that the success of FNAC highly depends on the training and experience of the personnel conducting the procedure [28,29].…”
Section: Discussionsupporting
confidence: 74%
“…FNAC is an excellent diagnostic tool for HIV-positive patients with lymphadenopathy. It is a routine examination that is cheap, quick, safe, free of complications, well tolerated by the patient, and highly accurate [1]. The smear can be evaluated immediately and the procedure can be repeated several times to obtain further materials for diagnosis or special stains.…”
Section: Introductionmentioning
confidence: 99%
“…FNAC is an excellent diagnostic tool for HIV-positive patients with lymphadenopathy. It is a routine examination that is cheap, quick, safe, free of complications, well tolerated by the patient, and highly accurate [1].…”
Section: Introductionmentioning
confidence: 99%
“…Overall, this study supports the utility of FNAB in resource-limited settings and highlights the importance of training non-pathologists to perform the procedure effectively. 22…”
Section: Utility Of Fnab In Lmicsmentioning
confidence: 99%